Clinical characteristics of lower extremity deep vein thrombosis in young vs. middle-aged adults: a single-center retrospective study - Zhang, Yaqiu; Wei, Haijun; Liu, Yang; Wang, Qiqi; He, Chunshui (Frontiers in Cardiovascular Medicine, 2024)
Background The incidence of deep vein thrombosis (DVT) in the lower extremities is increasing in the younger population. However, there are fewer reported comparisons in the literature for lower extremity DVT. Methods Patients aged <40 years admitted with lower-extremity DVT between January 2018 and December 2023 were retrospectively analyzed and followed up for 1 year. Results A total of 61 patients were included in the study and divided into two groups: 33 patients over 30 years of age (middle-aged group) and 28 patients under 30 years of age (young group). A significant gender difference was observed, with a higher proportion of males in the young group compared to the middle-aged group (P < 0.001). Five patients in the young group were treated with anticoagulation alone, whereas all patients in the middle-aged group underwent endovascular therapy. A higher prevalence of inferior vena cava thrombosis in the young group compared to the middle-aged group (60.71% vs. 33.3%, P = 0.032). The proportion of iliac vein stenosis was significantly higher in the middle-aged groups than in the young group (P = 0.002). There was no statistically significant difference in venous function scores (Villalta and rVCSS) between the two groups during both the preoperative period and the postoperative follow-up (P > 0.05). The incidence of lower-extremity DVT post-thrombotic syndrome and thrombus recurrence was higher in the young group than in the middle-aged group at 1 year postoperatively (PTS: 78.57% vs. 33.3%, P < 0.001, and thrombus recurrence: 28.57% vs. 9.09%, P < 0.05). Univariate and multivariate analyses revealed that inferior vena cava thrombosis was an independent risk factor for severe DVT post-thrombotic syndrome and recurrent DVT (P < 0.05), whereas gender was an independent risk factor for recurrent DVT (P < 0.05). Conclusions This study suggests differences in the clinical characteristics and prognosis of lower-extremity DVT.